Therapeutic Impacts of Tocotrienols and Boerhaavia diffusa on Cholesterol Dynamics, Lipid Hydroperoxidation and Antioxidant status on Hyperlipidemic Rats: Induced by Oxidized Cholesterol - Fouzia Ishaq3, Samir Chettri2, and Deepti Malhotra4, Amir Khan1,*, Abhay Singh Chandel2 (Recent Research in Science and Technology, 2011)
Cholesterol, the prominent member of steroid family, present in tissues and in plasma either as free cholesterol or as a storage form combined with a long chain fatty acid as cholesteryl ester. High blood cholesterol results in Atherosclerosis, which is characterized by presence of atheromas. In this we investigated the efficacy of antioxidant and hypolipidemic agents Tocotrienols and Boerhaavia diffusa by analyzing all the parameters in plasma lipoprotein lipids, TL, TC, TG, VLDL-C, LDL-C, non-HDL-C, MDA and in-vitro oxidizability of LDL, as investigated in oxidized cholesterol feeded rats treated with and without Tocotrienols and Boerhaavia diffusa. All the plasma lipids parameters, TL, TC, TG, VLDL-C, LDL-C, non-HDL-C and MDA levels were significantly increased in hyperlipidemic control rats. After 4 weeks administration of Tocotrienols and Boerhaavia diffusa significantly reduced the overall oxidative burden and effectively ameliorated the above altered parameters.